Life quality of patients with chronic obstructive pulmonary disease - Jakubowska, Klaudia Olga; Sykut, Anna; Łopuszyńska, Marta; Kropornicka, Beata; Kościołek, Aneta (Journal of Education, Health and Sport, 2017)
Introduction and the aim: Chronic obstructive pulmonary disease (COPD) belongs to the group of the most frequent chronic diseases. The major, and at the same time the most crucial goal of the actions undertaken for patients with COPD, is increase in early detection of this disease which will contribute to the decrease in morbidity and mortality. The aim of the study was to assess the quality of life of patients with chronic obstructive pulmonary disease. Material and methods: The survey was conducted among 100 patients with recognized chronic obstructive pulmonary disease, treated in the Department of Pneumology, Oncology and Allergology, as well as in the Clinic of Pulmonary Diseases and Tuberculosis of the Independent Public Clinical Hospital no. 4 in Lublin as well as in ambulatory way. The research material was collected with help of the questionnaire - St George’s Respiratory Questionnaire (SGRQ) for patients with respiratory system diseases. Results: Data analysis shows that in the range of 50% to 100% there were 72 persons, which indicates low level of life quality. Among 96 respondents, the quality of life in the category "symptoms" fit in the range 50% to 100% while no one fit in the range 0% to 10% which means that none of the respondents has reached the best quality of life in this category. The category of the impact of the disease on daily life obtained the best assessment as 69 respondents fit in the range 50% to 100%. Conclusions: Majority of respondents assess their quality of life on rather low level. The lowest quality of life was obtained in the category "symptoms". The dyspnoea was the disease symptom that occurred most often among the respondents. Longer duration of the chronic obstructive pulmonary disease was related to the deterioration of patients’ quality of life.